Measurement of diffusion lung capacity (DLCO) in silicosis patients: Correlation with radiographic abnormalities on high-resolution CT scan chest - Dixit, Ramakant; Jalutharia, Jitendra; Gupta, Avinash; Mathur, Reena; Goyal, Mukesh; Gupta, Neeraj; Chaudhary, Pradeep; Tiwari, Tarun (Lung India, 2022)
Objective: This study was conducted to evaluate diffusion capacity of lung for carbon monoxide (DLCO) in patients with simple and complicated silicosis and to correlate abnormal findings detected, if any, with the computed tomography abnormalities in these patients. Methods: This study included 56 patients with simple and complicated silicosis and without tuberculosis, in whom we performed DLCO as per standard technique. Various computed tomography findings, that is, presence, size and distribution of nodules associated with relative parenchymal and vascular markings, were recorded in the study subjects and classified into standard grading to be finally compared with DLCO. Visual grading score system was used to describe the extent of emphysematous changes based on the area of abnormally low attenuation, vascular disruption, bullae and so on and data were recorded. Results: Results showed that 85.7% patients had small opacities of varying grades and 28.5% showed large opacities, with 16% of them having type 'C' large opacities. The mean DLCO (% predicted) of patients with category '0' high-resolution computed tomography (HRCT) abnormality was 92.3 ± 6.8 (within normal limits), and this gradually decreased with increasing HRCT category to 44.2 ± 11.2 in grade '4' of progressive massive fibrosis (PMF) patients in this study (P < 0.01). This reflects a significant inverse correlation between visual HRCT category and the DLCO % predicted (r > −0.89, P < 0.001). The mean DLCO (% predicted) was 51 ± 12.6 in patients with grade '1' emphysema in HRCT, 53 ± 13.5 in grade '2', 43 ± 6.4 in grade '3' and 37.7 ± 6.3 in grade '4'; however, there was no correlation between emphysema grading and pulmonary functional index (r = −0.33, P = 0.15). Conclusion: This study observed significant abnormality in DLCO among silicosis patients and its strong correlation with the extent of radiological abnormality. HRCT finding of large opacities could be an important indicator of the severity of silicosis, as reflected by significantly reduced DLCO in such patients.